Operational experience and behaviour of a parabolic trough collector system with concrete thermal energy storage for process steam generation in Cyprus - Sattler, Johannes Christoph; Caminos, Ricardo Alexander Chico; Ürlings, Nicolas; Dutta, Siddharth; Ruiz, Victor; Kalogirou, Soteris A.; Ktistis, Panayiotis K.; Agathokleous, Rafaela; Jung, Christian; Alexopoulos, Spiros; Atti, Vikrama; Boura, Cristiano Teixeira; et al. (My University, 2020)
As part of the transnational research project EDITOR, a parabolic trough collector system (PTC) with concrete thermal energy storage (C-TES) was installed and commissioned in Limassol, Cyprus. The system is located on the premises of the beverage manufacturer KEAN Soft Drinks Ltd. and its function is to supply process steam for the factory’s pasteurisation process [1]. Depending on the factory’s seasonally varying capacity for beverage production, the solar system delivers between 5 and 25 % of the total steam demand. In combination with the C-TES, the solar plant can supply process steam on demand before sunrise or after sunset. Furthermore, the C-TES compensates the PTC during the day in fluctuating weather conditions. The parabolic trough collector as well as the control and oil handling unit is designed and manufactured by Protarget AG, Germany. The C-TES is designed and produced by CADE Soluciones de Ingeniería, S.L., Spain. In the focus of this paper is the description of the operational experience with the PTC, C-TES and boiler during the commissioning and operation phase. Additionally, innovative optimisation measures are presented.
Keywords: Τhermal energy storage; Solar plant